The effect of alkyl chain and electronegative atoms in anion on biological activity of anilinium carboxylate bioactive ionic liquids and computational approaches by DFT functional and molecular docking. Issue 7 (July 2021) - Kumer, Ajoy; Khan, Md. Wahab
Abstract: The Brønsted acid-base neutralization was executed for synthesis of the anilinium carboxylate ionic liquids (ACILs), and obtained highly viscous liquids with yields about (90–94)%. These ILs were purified by distillation process and used vacuum oven, as well as characterized by FT-IR, UV spectroscopy and 1H-NMR. To evaluate the antimicrobial activity, the well diffusion method was used against eight human pathogenic bacteria, showing inhibition of zone at 13 mm–27 mm, and three fungi with result about 60%. Plus, the DFT functional from material studio 8.0 was used for evaluation of computational screening for estimating the chemical reactivity, HOMO, LUMO and HOMO-LUMO gap, recorded from -7.252 to -8.20 kcal/mol. The IL05 has showed about -6.5 kcal/mol docking score as standard inhibitor, as and higher than starting. Form AMDET properties, it has revealed that they have low toxicity, higher absorption through the biological system and non-carcinogenic. Finally, the electronegative groups, such as F, Cl and Br atoms in anion can show the higher antimicrobial activity and molecular docking score among all others while F atom containing IL05 shows the highest docking score and antimicrobial activity. However, it is concluded that rather than long large alkyl chain of anion, F atom (the highest electronegative atom) containing anion is better for biologically significance ILs. Abstract : Ionic liquids, Antimicrobial activity, Well-diffusion method, DFT, HOMO, LUMO and ADMET